Gas Pressure Measurement Device and Medical Vacuum Design - Padang Tunggal, Tatiya; Sanjaya, Alfana; Agus Widodo, Hendro; Kunal, Kunal; Thanh Nguyen, Phong (Universitas Muhammadiyah Yogyakarta, 2020)
Two methods are used in a digital pressure meter available in the market, namely positive pressure, and negative pressure. The positive one is used to measure the air pressure on a sphygmomanometer and medical gas pressure at an outlet in the treatment room so that operators can easily check medical gas pressure for the safety of the patient, or they can routinely check to find out how much pressure of the medical gas. Based on the background, the research aimed to design a digital pressure meter equipped with a medical gas measurement mode so that the device can be used to calibrate the sphygmomanometer, suction pump, and measure the medical gas pressure available at the medical gas outlet in each treatment room.